Predictive Factors for Extrathyroidal Extension of Papillary Thyroid Carcinoma Based on Preoperative Sonography. (1st February 2014) - Lee, Chang Yoon; Kim, Soo Jin; Ko, Kyung Ran; Chung, Ki-Wook; Lee, Joo-Hyuk
Abstract : Objectives: The purpose of this study was to evaluate the diagnostic performance and predictive factors of extrathyroidal extension of papillary thyroid carcinoma based on preoperative sonography. Methods: Preoperative sonography was performed for 568 patients who underwent surgery for papillary thyroid cancer between May 2009 and December 2010. Patients' T stages based on preoperative sonography were compared with their T stages based on pathologic examination, and we statistically analyzed the discriminatory performance of sonography. Among the 568 patients enrolled in this study, we selected 320 patients in whom extrathyroidal extension was suspected on sonography. We analyzed several predictive factors for extrathyroidal extension. Results: Two hundred seventy‐five of the 568 patients were proven to have pathologic extrathyroidal extension of papillary thyroid cancer after surgery (75.9% diagnostic accuracy, 83.3% sensitivity, 68.9% specificity, 71.6% positive predictive value, and 81.5% negative predictive value). Of 320 patients with sonographically suspected extrathyroidal extension, a larger lesion size ( P < .001) and a higher lymph node stage on sonography ( P = .004) were the best predictors of extrathyroidal extension among the features that we measured. There were no significant differences in terms of the lesion site or thyroid parenchymal background echogenicity. Thyroid capsular protrusion had a higher predictive value than the abutting ratio ( P = .001). However, increasing the abutting ratio enabled the prediction of extrathyroidal extension on sonography ( P = .009). Conclusions: Preoperative sonography is a helpful tool for predicting pathologic extrathyroidal extension of papillary thyroid cancer. In particular, clinicians should focus on the lesion size, nodal stage, and abutment or capsular protrusion of the lesion while performing sonography because these are the most useful predictive factors for extrathyroidal extension.